2022
DOI: 10.1007/s40487-022-00187-3
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Impact of Delayed Access to Oncology Drugs on Patient Outcomes in Canada

Abstract: Introduction New requirements in Canada’s pricing processes for patented drugs may exacerbate delays in regulatory and reimbursement reviews. This study seeks to better understand the impact of any additional delays on non-small cell lung cancer (NSCLC) patients by measuring the following: (a) durations and outcomes of regulatory and reimbursement reviews of NSCLC drugs in Canada and reference countries; (b) delays in Canada’s reviews of three NSCLC drugs (nivolumab, afatinib, and pemetrexed [NAP]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…Of those, 96 were excluded. Snowballing methods yielded two additional records, and therefore, four unique records were included in the TLR [ 13 , 14 , 15 , 16 ]. The study selection process is depicted in the PRISMA flow chart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of those, 96 were excluded. Snowballing methods yielded two additional records, and therefore, four unique records were included in the TLR [ 13 , 14 , 15 , 16 ]. The study selection process is depicted in the PRISMA flow chart ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The four articles reporting systemic delays were a retrospective cohort study [ 15 ], a public data analysis [ 13 , 14 ] and an analysis of literature and empirical modelling [ 16 ]. Multiple types of cancer were assessed in most studies [ 15 ], while the study by Vanderpuye-Orgle only assessed non-small cell lung cancer (NSCLC) [ 16 ]. Two studies were from Canada [ 13 , 14 ], while the other two studies were from multiple countries [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…32 Another recent study evaluating the impact of delays in Canada's regulatory and reimbursement reviews of medications for lung cancer revealed a significant decrease in person-years of life, qualityadjusted life-years and productivity losses. 33 How the inequities identified in the present study affect regional differences in survival with mRCC is beyond the scope of this paper but does raise an important question for future studies.…”
Section: Cuaj -Original Researchmentioning
confidence: 89%